Memórias literárias : um objeto de ensino da leitura na perspectiva do interacionismo sociodiscursivo - Andrade, Vanuzia Vieira de (2019)
The present research aims to investigate reading strategies with the genre of literary memories from four chapters - Natalia Savishna, Childhood, Grief and Sad Recollections - from the first part of the trilogy Childhood, Boyhood, and Youth of the Russian writer Leo Tolstoy. The reading approach follows the theoretical-pistemological perspective of Sociodiscursive Interactionism (SDI) defended by Bronckart (2007). We start from the assumption that the productive reading of the literary memories genre is linked to the reader's observation of the discursive worlds intersection of the exposing and narrating’s order, through the spatiotemporal construction of the enunciation promoted by the producing agent of the text in a autobiographical discourse. Literary memories promote a narration of facts from one's private life while revealing historical, cultural, and social contexts in a society. In the writing of the literary memories genre, we observe that there is a certain discontinuity in the narrative and this configures changes of spatiotemporal relations promoted by the narrator. These phenomena can be observed through the projections of verbal tenses identified as narrated world and commented world belonging to Weinrich's sociocommunicative theory (1968). From an action research, based in Thiollent (2011), we developed an intervention in an 8th grade class of a school in the municipal public network of Paripiranga-BA. After learning about the difficulties that students have to carry out proficient reading text, we propose the elaboration of a Reading Teaching Sequence based on the postulates of Dolz, Noverraz and Schneuwly (2011) and an interactive reading class proposed by Leurquin (2014), aiming to contribute to the development of students language skills, according to Dolz, Pasquier and Bronckart (2017) and Dolz and Schneuwly (2011). Data collected generated a pedagogical book for the practice of literary memories reading in the classroom, aiming to cooperate with teaching practices that are associated to a sociocommunicative perspective of the Portuguese language teaching.